Baby-friendly initiative: a blueprint to enable breastfeeding in hospital settings - Shrivastava, Saurabh R.; Shrivastava, Prateek S.; Ramasamy, Jegadeesh (International Journal of Contemporary Pediatrics, 2017)
Worldwide, breastfeeding has been regarded as one of the most effective ways to ensure adequate health and survival of the child. In fact, World Health Organization (WHO) has proposed the practice of exclusive breastfeeding till the child attains age of six months as more than a million infant deaths have been reported globally in its absence. Multiple studies have revealed confirmatory evidences that breastfeeding is advantageous for both the mother and the child. Further, it has been estimated that an additional 1.5 million lives of under five children would be saved every year if all newborns are exclusively breastfed for first six months of their life.